An association between sudden infant death syndrome (SIDS) andHelicobacter pylori infection. Issue 5 (1st November 2000) - Kerr, J R; Al-Khattaf, A; Barson, A J; Burnie, J P
Abstract : BACKGROUND: Helicobacter pylori has recently been detected in the stomach and trachea of cases of sudden infant death syndrome (SIDS) and proposed as a cause of SIDS. AIMS: To establish the incidence of H pylori in the stomach, trachea, and lung of cases of SIDS and controls. METHODS: Stomach, trachea, and lung tissues from 32 cases of SIDS and eight control cases were examined retrospectively. Diagnosis of SIDS was based on established criteria. Controls were defined by death within 1 year of age and an identifiable cause of death. Tissues were examined histologically for the presence of bacteria. Extracted DNA from these tissues was tested for H pylori ureC and cagA sequences by nested polymerase chain reaction and amplicons detected by enzyme linked immunosorbent assay (ELISA). The cut off for each ELISA for each of the tissue types was taken as the mean optical density plus two times the standard deviation of a range of negative controls. RESULTS: Ages of SIDS cases ranged from 2 to 28 weeks. Ages of controls ranged from 3 to 44 weeks. For the ureC gene, 25 SIDS cases were positive in one or more tissues compared with one of the controls. For the cagA gene, 25 SIDS cases were positive in one or more tissues compared with one of the controls. CONCLUSIONS: There is a highly significant association between H pylori ureC and cagA genes in the stomach, trachea, and lung of cases of SIDS when compared with controls.